Russia’s Energy Sovereignty: Vladimir Putin’s Leadership Autarky and its Relevance to Indonesia’s National Defense - Hermawan, Dadang; Pinandito, Prasetyo; Susilo, Tarsisius; Saroso, Budi; Limbong , Benny Leonardo (CV. Publikasi Indonesia, 2025)
Russia's energy sovereignty under Vladimir Putin demonstrates how strategic resource control can serve as both a foundation for national defense and a tool for geopolitical influence. This study examines Putin's autarky leadership model—characterized by centralized energy governance, economic nationalism, and the integration of energy policy with military strategy and explores its relevance to Indonesia's defense modernization toward Golden Indonesia 2045. Using a qualitative descriptive approach with library research methodology, this study analyzes secondary data from government documents, defense white papers, and academic literature published between 2015-2025. The analysis reveals that Putin's leadership consolidates energy (oil and natural gas) as a dual instrument: funding defense modernization and enabling coercive diplomacy, particularly through pipeline projects like Nord Stream. This approach combines classical realism with economic nationalism to reduce external dependency and maintain strategic autonomy. For Indonesia, the study identifies critical lessons: the necessity of integrating energy independence with defense doctrine, developing a resource-based defense industry, and establishing ethical leadership frameworks rooted in Pancasila values. Key recommendations include: strengthening national energy policy as a defense asset, promoting local content in defense technology, designing an adaptive defense doctrine based on natural resource sovereignty, and building energy diplomacy to enhance Indo-Pacific stability. Unlike Russia's centralized autarky, Indonesia's model should emphasize collaborative sovereignty balancing national independence with democratic accountability, environmental sustainability, and social justice. This research contributes to strategic leadership literature by connecting energy geopolitics with defense philosophy in an ASEAN context.